2020
DOI: 10.3168/jds.2019-17159
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of whey proteins in the colostrum and mature milk of Xinong Saanen goats

Abstract: Xinong Saanen goats are among the major dairy goats in China, and their milk is one of the major milk supplies for the Chinese dairy industry. To explore the whey proteome of Xinong Saanen goat milk, we analyzed the whey proteins of goat colostrum and mature milk using proteomic techniques. We identified a total of 314 and 524 proteins in goat colostrum and mature milk, respectively. Our data showed the first 3 functional categories of signal, disulfide bond, and secreted in both milk types. The most abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…Results indicated that these proteins mainly belonged to the biological process "response to stress," the cellular component "extracellular region," and the molecular function "binding." As shown in Figure 2a, most differentially expressed proteins (35%) were involved in the biological process of response to stress, followed by (Hurley and Theil, 2011;Beck et al, 2015;Sun et al, 2020). The results of the present study suggested that goat milk whey proteins differed in immune defenserelated functions such as stress, defense, inflammation, Accession number = unique entry name assigned for a given protein according to the Uniprot database (https: / / www .uniprot .org/ ).…”
Section: Go Analysismentioning
confidence: 63%
See 3 more Smart Citations
“…Results indicated that these proteins mainly belonged to the biological process "response to stress," the cellular component "extracellular region," and the molecular function "binding." As shown in Figure 2a, most differentially expressed proteins (35%) were involved in the biological process of response to stress, followed by (Hurley and Theil, 2011;Beck et al, 2015;Sun et al, 2020). The results of the present study suggested that goat milk whey proteins differed in immune defenserelated functions such as stress, defense, inflammation, Accession number = unique entry name assigned for a given protein according to the Uniprot database (https: / / www .uniprot .org/ ).…”
Section: Go Analysismentioning
confidence: 63%
“…All animals were healthy, and all milk samples were from the first batch milk in the early morning. Whey protein samples from both goat and cow milk were extracted based on a previously reported method (Sun et al, 2020). Briefly, 30 goat milk samples and 30 cow milk samples were mixed separately.…”
Section: Preparation Of Whey Protein Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the latest study, the addition of quinoa extraction to goat milk yogurt enhanced the quality of the final products in terms of apparent viscosity, microstructure and organoleptic acceptability (El‐Shafei et al ., 2019). As a protein that plays an important role in functional dairy products, casein (CN) is one of the most abundant proteins in goat milk, accounting for approximately 70% of the total protein (Sun et al ., 2020), and the content of casein can change over time during the lactation period (Chen et al ., 2018; Mal et al ., 2018). CN is responsible for most of the unique physical properties of milk.…”
Section: Introductionmentioning
confidence: 99%